WHIM-3D-QSPR APPROACH FOR PREDICTING AQUEOUS SOLUBILITY OF CHLORINATED HYDROCARBONS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT The weighted holistic invariant molecular-three dimensional-quantitative structure property relationship (WHIM- 3D-QSPR) approach has been applied to the study of the aqueous solubility (- log Sw) of chlorinated hydrocarbon compounds (CHC's). The obtained QSPR model is predictive and only requires four WHIM-3D descriptors in the calculation. The correlation equation of the model that is based on a training set of 50 CHC's compound has statistical parameters: standard coefficient correlation (~) =0.948